A TRIBO DE ISSACAR Uma tribo de assalariados - Jr., Roberto Rodrigues de Andrade (2012)
This bibliographic work brings Issachar‟s tribe as its main theme. This tribal group is part of Israel‟s social system since its beginning and has as a main feature the hard life of the man who works for a living, as well as many others in the mankind history, except that, inside the Israel‟s tribal society, this tribe had a difference to give up the possibility of live free from the Egyptian and the Cananeus domination, this is due to the fact that they found themselves in a hard living region for it seemed to be a satisfying and safe place. In compensation this paradise‟ demanded hard work and sweat and at the end gave them the curious name of the wage-earning man tribe. Spend one‟s life without any struggle against their oppressors wasn‟t an easy decision, but among them earn his life and bread. Israel‟s history, far away of being repetitious and determinant is an intriguing and fascinating history due to its possibilities of discover inside Israel‟s people the exciting new life‟ that God, the life bearer, wishes to offer to anyone who knows to live. Work is not penalty, work is blessing, work is sacred and cherishes of horizons the agreed time of living. Supported on texts from Jdg19, 17-23; Gen 49, 14-15; and Dt 33, 18-19; we shall try to find the audacity of a social group that decide to live in odd manner, in a poor and difficult region geographically speaking; a social group that decide to make from its own working power‟ the instrument that assures them to be wherever they want, and do whatever that pleasures them. This is Issachar.